2017
DOI: 10.1002/cmdc.201700271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Glycyrrhetic Acid Derivatives as Potential VEGFR2 Inhibitors

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) has been proven to play a major role in the regulation of tumor angiogenesis. A series of novel glycyrrhetic acid derivatives were synthesized and evaluated for their VEGFR2 inhibitory activity as well as their antiproliferative properties against four cancer cell lines (MCF-7, HeLa, HepG2, and A549). In vitro biological evaluations against these human tumor cell lines indicate that most of the prepared compounds have antiproliferative activities; compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Compound 41 also showed potent inhibitory activity against vascular endothelial growth factor receptor 2 (VEGFR2) tyrosine kinase, with an IC 50 value of 0.35 mM. Docking simulations were performed to discover the binding mode, and the results indicated that compound 41 could bind well to VEGFR2 at the active site 66 .…”
Section: Biological Effects Of Natural Products Containing the Piperazinyl Moietymentioning
confidence: 99%
“…Compound 41 also showed potent inhibitory activity against vascular endothelial growth factor receptor 2 (VEGFR2) tyrosine kinase, with an IC 50 value of 0.35 mM. Docking simulations were performed to discover the binding mode, and the results indicated that compound 41 could bind well to VEGFR2 at the active site 66 .…”
Section: Biological Effects Of Natural Products Containing the Piperazinyl Moietymentioning
confidence: 99%
“…In addition, GA 1 can be extracted from the roots of licorice in high yields (up to 24%) [22]. These findings have increased its scientific interest as a scaffold for the development of new derivatives for potential cancer treatment [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the C-30 carboxyl group is often esterified or amidated in order to enhance the antitumor or other efficacy of 18βglycyrrhetinic acid derivatives [11]. A novel piperazinyl amide b exhibits the optimal inhibitory activity against MCF-7 and can be further developed as a potent VEGFR2 and antitumor agent [12].…”
Section: Introductionmentioning
confidence: 99%
“…These two methods are complicated through the side formation of bisamide, obviously, due to the competitive attack on the N atoms of the symmetric diamine. An alternative method [12] to prepare such piperazinyl amides (c) involves the amidation of 18β-glycyrrhetinic acid with 4-substituted phenylpiperazines in the presence of N,N-dicyclohexylcarbodiimide (DDC) and HOBt. Under such reaction conditions, the bisamide as byproduct can be evitable, whereas the substituted piperazine compounds will not be readily available.…”
Section: Introductionmentioning
confidence: 99%